Transcriptional Regulation of Glucose Metabolism: The Emerging Role of the HMGA1 Chromatin Factor - Chiefari, Eusebio; Foti, Daniela P.; Sgarra, Riccardo; Pegoraro, Silvia; Arcidiacono, Biagio; Brunetti, Francesco S.; Greco, Manfredi; Manfioletti, Guidalberto; Brunetti, Antonio (Frontiers in Endocrinology, 2018)
HMGA1 (high mobility group A1) is a nonhistone architectural chromosomal protein that functions mainly as a dynamic regulator of chromatin structure and gene transcription. As such, HMGA1 is involved in a variety of fundamental cellular processes, including gene expression, epigenetic regulation, cell differentiation and proliferation, as well as DNA repair. In the last years, many reports have demonstrated a role of HMGA1 in the transcriptional regulation of several genes implicated in glucose homeostasis. Initially, it was proved that HMGA1 is essential for normal expression of the insulin receptor (INSR), a critical link in insulin action and glucose homeostasis. Later, it was demonstrated that HMGA1 is also a downstream nuclear target of the INSR signaling pathway, representing a novel mediator of insulin action and function at this level. Moreover, other observations have indicated the role of HMGA1 as a positive modulator of the Forkhead box protein O1 (FoxO1), a master regulatory factor for gluconeogenesis and glycogenolysis, as well as a positive regulator of the expression of insulin and of a series of circulating proteins that are involved in glucose counterregulation, such as the insulin growth factor binding protein 1 (IGFBP1), and the retinol binding protein 4 (RBP4). Thus, several lines of evidence underscore the importance of HMGA1 in the regulation of glucose production and disposal. Consistently, lack of HMGA1 causes insulin resistance and diabetes in humans and mice, while variations in the HMGA1 gene are associated with the risk of type 2 diabetes and metabolic syndrome, two highly prevalent diseases that share insulin resistance as a common pathogenetic mechanism. This review intends to give an overview about our current knowledge on the role of HMGA1 in glucose metabolism. Although research in this field is ongoing, many aspects still remain elusive. Future directions to improve our insights into the pathophysiology of glucose homeostasis may include epigenetic studies and the use of “omics” strategies. We believe that a more comprehensive understanding of HMGA1 and its networks may reveal interesting molecular links between glucose metabolism and other biological processes, such as cell proliferation and differentiation.